Twenty aspects of emptiness in Prajnaparamita Buddhism - Strelkova, Anastasia (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2015)
This article examines the canonical list of “twenty kinds of emptiness (śūnyatā)” in рrajñāpāramitā Buddhism. The meaning of every one of them is determined by the means of comparative analysis of the texts of Chinese Buddhist canon (Chinese versions of prajñāpāramitāsūtra, Vasubandhu, Nāgārjuna and a treatise of a later Tiantai thinker Zhi-yi). All the basic variants of Chinese terms used by the Chinese Buddhists in the process of translation from Sanskrit are listed together and their different semantic variations are analyzed. In spite of the fact that the most popular was the expression “twenty emptinesses” there are lists of fourteen, sixteen, eighteen positions, and Chinese Buddhists considered the list of “eighteen emptinesses” to be the most basic one. This may support a suggestion made by researchers concerning later origin of the list with twenty positions. Besides this, the order of positions in the list in different sources is not identical. This is often due to the efforts of the Buddhist authors to find in this list a logical succession based mostly on gnoseological approach (emptiness of subject of perception, emptiness of object of perception etc.). But independently of differences in the lists of “kinds of emptiness” and different variants of their translation and interpretation in the Buddhist tradition, the emptiness is only one – śūnyatā, serving all the different lists of “emptinesses” merely to make easier the perception of the ideas of śūnya-vāda as an example of applying the principle of emptiness (illusiveness, unreality) to different groups of objects. Therefore it is more correct to speak rather about twenty aspects of emptiness, than about twenty kinds of it.